2016
DOI: 10.1111/edt.12303
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration in mandibular fractures after the application of autologous mesenchymal stem cells, a randomized clinical trial

Abstract: Similar ossification values were obtained after 4 weeks when the use of AMSCs was compared to simple fracture reduction. However, after 12 weeks, the AMSCs group had a 36.48% higher ossification rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…The quality assessment of the included studies revealed an unknown risk of bias (for one or more key domains) for the majority of included studies [4,6,7,9,10-12,33,34], two studies [5,8] was classified as low risk (of bias for all key domains) (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Castillo-Cardiel et al [5] performed randomized clinical trial on 20 humans to evaluate regeneration time and to increase bone quality by testing effectiveness of AMSCs from adipose tissue application in mandibular angle fractures. Patients were divided into 2 groups while only 1 group the Study Group passes reduction with application of AMSCs, and the Control Group passed only simple fracture reduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations